Auto- and non-auto transferable R-plasmids in some Salmonella strains - VERMA, J C; GUPTA, B R (The Indian Journal of Animal Sciences, 2013)
Occurrence ofhoth auto- and non-auto transfer system of drug resistance were studied in 1 strain each of S. anatwn and S. typhimurium. These 2 strains were identified during in vitro transfer of drug resistance carried out with R4 Salmonella strains. On mobilization 5 of 7 and 6 of 7 drug resistance markers were mobilizable while only one marker ’Su’ was transferrable in direct cross in both the strains of Samonella.